22nd AIAA Computational Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-2609
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Incompressible Separated Turbulent Flows around Two-Dimensional Bodies with URANS Models in OpenFOAM

Abstract: The goal of this study is to determine whether an unsteady formulation of a RANS turbulence model leads to improved description of incompressible separated turbulent flows around two-dimensional bodies. Two geometries are considered: a NACA 4412 airfoil and a circular cylinder. Simulations are conducted with two-equation turbulent models: Menter's 1994 Shear Stress Transport model and Wilcox's 2006 -model, implemented in the opensource CFD OpenFOAM software. Comparison with experimental data and computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(52 reference statements)
2
0
0
Order By: Relevance
“…However, the present predicted values were close to those reported by Porteous et al (2015) [33] and Pang et al (2016). The value of St was higher than the value predicted by Porteous et al (2015) [33] but close to the data reported by Ong et al (2009), Pang et al (2016) [34] and Janocha et al ( 2021) [35]. To sum up, a general agreement with the published data could be achieved by the present numerical model.…”
Section: Mesh Convergence and Validation Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…However, the present predicted values were close to those reported by Porteous et al (2015) [33] and Pang et al (2016). The value of St was higher than the value predicted by Porteous et al (2015) [33] but close to the data reported by Ong et al (2009), Pang et al (2016) [34] and Janocha et al ( 2021) [35]. To sum up, a general agreement with the published data could be achieved by the present numerical model.…”
Section: Mesh Convergence and Validation Studiessupporting
confidence: 91%
“…However, the C L,rms , which was more sensitive than the value of C D , was different from the obtained value of C L,rms reported by Ong et al (2009) [2], where the k − ε turbulence model was applied. However, the present predicted values were close to those reported by Porteous et al (2015) [33] and Pang et al (2016). The value of St was higher than the value predicted by Porteous et al (2015) [33] but close to the data reported by Ong et al (2009), Pang et al (2016) [34] and Janocha et al ( 2021) [35].…”
Section: Mesh Convergence and Validation Studiessupporting
confidence: 90%